2018
DOI: 10.3389/fmicb.2018.03025
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus gasseri LA39 Activates the Oxidative Phosphorylation Pathway in Porcine Intestinal Epithelial Cells

Abstract: Intestinal microbial interactions with the host epithelium have important roles in host health. Our previous data have suggested that Lactobacillus gasseri LA39 is the predominant intestinal Lactobacillus in weaned piglets. However, the regulatory role of L. gasseri LA39 in the intestinal epithelial protein expression in piglets remains unclear. In the present study, we conducted comparative proteomics approach to investigate the intestinal epithelial protein profile alteration caused by L. gasseri LA39 in pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Importantly, the genome encoded 3 gene clusters (JM1_GM000623-JM1_GM000640, JM1_GM001955-JM1_GM001967, and JM1_GM002030-JM1_GM002041) for bacteriocin biosynthesis. The results indicated that L. gasseri JM1 possessed the capacity to resist oxidative stress and synthesize bacteriocin, which was in accordance with previous reports (Zorič Peternel et al, 2010;Maldonado-Barragán et al, 2016;Hu et al, 2018). Compared with other L. gasseri strains, the genetic relationship of L. gasseri JM1 with 4M13 and K7 is closer, which may associate to the origin.…”
Section: Discussionsupporting
confidence: 90%
“…Importantly, the genome encoded 3 gene clusters (JM1_GM000623-JM1_GM000640, JM1_GM001955-JM1_GM001967, and JM1_GM002030-JM1_GM002041) for bacteriocin biosynthesis. The results indicated that L. gasseri JM1 possessed the capacity to resist oxidative stress and synthesize bacteriocin, which was in accordance with previous reports (Zorič Peternel et al, 2010;Maldonado-Barragán et al, 2016;Hu et al, 2018). Compared with other L. gasseri strains, the genetic relationship of L. gasseri JM1 with 4M13 and K7 is closer, which may associate to the origin.…”
Section: Discussionsupporting
confidence: 90%
“…Growing evidence suggests that the gut microbiota regulate host energy metabolism. Our previous study demonstrated that Lactobacillus gasseri LA39 may act as a potential probiotic and stimulates energy production in early-weaned piglets [21]. The present study provides new insights into the effects of L. frumenti to increase the β-oxidation of fatty acid in the liver of early-weaned piglets.…”
Section: Discussionmentioning
confidence: 58%
“…V-type proton ATPase subunit a (protein accession number H0YEL3, FC = 0.00) was markedly damaged by CRA, although it is closely related to energy production promotion and confers health-promoting functions in porcine intestinal epithelial cells [ 28 ]. Upregulation (FC = 1.82) of the mitochondrial inner membrane protein OXA1L (protein accession number E7EVY0) effectively promotes the assembly of multiple respiratory chain complexes [ 29 ], while increasing the expression (FC = 1.88) of glutamate-cysteine ligase modifier (GCLM) (protein accession number P48507), which promotes the expression of GSH.…”
Section: Discussionmentioning
confidence: 99%